The impact of hedge accounting on a firm market value - Lenka Čiperová (European Financial and Accounting Journal, 2024)
In 2018, the International Accounting Standards Board (IASB) introduced International Financial Reporting Standard 9 (IFRS 9), which sets out principles for hedge accounting and replaces International Accounting Standard 39 (IAS 39). IFRS 9 aims to provide better information about companies' risk management policies by simplifying reporting requirements and improving risk disclosures compared to IAS 39. The objective of hedge accounting is to facilitate investors' understanding of companies' risk management strategies and provide information on the effectiveness of hedging. In this study, we attempt to determine how hedge accounting fulfils the IASB's objective and whether better risk management information translates into value attributed by investors. In the empirical part of this study, a firm valuation framework is used to analyse the impact of hedge accounting on the market value of a sample of Polish companies listed on the Warsaw Stock Exchange. The results show the positive effect of using hedge accounting, suggesting that information about risk management strategies can positively affect investors' valuation of the firm. The results also show that the simplified reporting requirements under IFRS 9 motivated companies that used hedge accounting to switch to the new accounting standard but, contrary to expectations, did not motivate new companies to adopt hedge accounting.
Keywords: M41; M48; 650; Firm Market Value; Hedge Accounting; IFRS 9; Risk Management